Transformasi Audit Kinerja dari Pengawasan Administratif menjadi Instrumen Peningkatan Kinerja Organisasi dan Perbaikan Kebijakan Publik: Studi pada PDAM Sumatera Utara - Rika Nurselinda; Rara Ivanka; Saima Hotnasari Harahap; M. Irsan Nasution (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Performance audit has long been perceived as an administrative oversight mechanism oriented toward compliance and error detection. In fact, its essence is to encourage continuous improvement and increase organizational added value. This study examines the transformation of performance audits into an instrument for improving organizational performance effectiveness and public policy advancement, focusing on the preparation of Audit Result Reports (LHP), obtaining feedback on recommendations and responses, and the preparation and submission of LHPs at Regional Drinking Water Companies (PDAMs) in North Sumatra. This study, which uses a qualitative approach through a case study technique at PDAM Tirtanadi in North Sumatra Province, identifies three key challenges in the transition of performance audits: (1) the preparation of the Audit Report remains procedural without strategic impact analysis; (2) audit recommendations lack constructiveness, resulting in formalistic management responses and follow-up; (3) the delivery of the Audit Report has not yet encouraged dialogue for policy improvement. This study recommends a performance audit transformation model through changes in auditor paradigm, preparation of risk-based and value-added recommendations, and participatory follow-up mechanisms.